Peningkatan Kualitas PBM Melalui Pelatihan Integrasi Model dan Aplikasi Teknologi Pembelajaran Kimia Inovatif Pada Guru-Guru Kimia - Florida Doloksaribu; Albaiti (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2025)
Chemistry learning is a learning that requires many innovative learning models to anticipate problems found in the field. For this reason, chemistry learning requires models, methods, techniques, approaches, and learning media that are integrated with each other, according to the needs of students, the character of the material and students, and what is currently developing that must be responded to by chemistry education. In the current rapid technological advances and learning models, there are still many conventional learning models. Teachers who are less creative will continue to occur as in the past and will continue to hinder the development of students in responding to innovative learning. This condition is often found in various schools in remote areas, where the internet network does not function optimally, so that the cause of the lack of innovative abilities, so that educators do not optimally accept the concept. The difficulties found in abstract chemistry material can be made easier by utilizing learning technology applications. Thus, educators not only get material manually and conventionally, but are integrated with various approaches. Based on the results of the training on the integration of innovative chemistry learning models and applications of technology for chemistry teachers from several Papua and Maluku regions, it resulted in an increase in the understanding of concepts and skills of teachers, and it is hoped that trained teachers will be able to improve the quality of innovative teaching and learning in their respective schools